(1-1/2)x(1-1/3)x1-1/4) (1+1/2):(1+1/3):(1+1/4)
=................................. =........................................
=................................. =.........................................
=................................. =............................................
(1-\(\frac{1}{2}\))x(1 - \(\frac{1}{3}\))x( 1 -\(\frac{1}{4}\)) (1+\(\frac{1}{2}\)) : ( 1+\(\frac{1}{3}\)) : ( 1 +\(\frac{1}{4}\))
=\(\frac{1}{2}\)x\(\frac{2}{3}\)x\(\frac{3}{4}\) =\(\frac{3}{2}\):\(\frac{4}{3}\):\(\frac{5}{4}\)
=\(\frac{1}{4}\) =\(\frac{9}{10}\)
Chúc bạn học tốt :)